EVALUATING ART IN BASIC EDUCATION: HISTORICAL AND CONCEPTUAL TENSIONS OF A DISCIPLINE UNDER CONSTRUCTION - Rodrigo Caldas, Felipe; Solange Stoeberl da Cunha, Daiane (Revista Gênero e Interdisciplinaridade, 2026)
This article discusses the problems of assessment in Art in Brazilian basic education, focusing on the historical-conceptual tensions that structure the problem. It starts from the hypothesis that such tensions are not accidental nor do they stem solely from the formative limitations of teachers, but are constitutive of the very configuration of the discipline in the school curriculum, heirs to the pedagogical currents that have successively shaped it. The perspective adopted is that of contemporary art/education, as characterized by Dias (2011), assumed as a theoretical horizon that recognizes the provisional nature of current practices and rejects the conceptual closure of previous currents. The analysis articulates the legal and curricular trajectory of the discipline, the pedagogical currents of art teaching and their distinct ways of (not) assessing, the multiple dimensions that can be assessed in artistic knowledge, the structural tensions that result from this, and the indication of evaluative paths consistent with the nature of the subject. This text engages with Brazilian literature on art education (Barbosa, 1991; Cunha, 2020; Ferraz; Fusari, 2010; Iavelberg, 2003), with Brazilian references on learning assessment (Cerqueira, 2022; Hoffmann, 1991, 1993; Luckesi, 1995), and with recent studies that address the topic within the context of the BNCC (Castro; Meira, 2025; Costa, 2016), particularly drawing on Hernández’s (2000) contribution on assessment in art education.